Interactive Pop-Up Storybooks as a Medium to Cultivate Tolerance in Early Childhood: A Local Wisdom Approach - Rizki Sevi Triana; Hisbiyatul Hasanah; Eva Aini Desta Ningsih; Indah Kharismawati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
Interactive learning media play a crucial role in promoting cognitive and social development in early childhood education. This study aims to develop an interactive pop-up storybook based on local wisdom as a medium to foster the value of tolerance in young children. Using the 4D Research and Development (R&D) model (Define, Design, Develop, Disseminate), the study involved children aged 4–6 years enrolled in early childhood education programs. The Define stage identified needs, analyzed curriculum alignment, and explored cultural relevance. The Design stage produced a prototype integrating local cultural values, interactive features, and multisensory elements to enhance engagement and understanding of social values. The Develop stage included validation of the prototype by experts in early childhood education, child psychology, and local wisdom, resulting in an overall validity score of 90.2% (highly valid), followed by a limited trial which showed significant improvements in engagement, social interaction, and children’s understanding of tolerance. The Disseminate stage evaluated the usability of the media by teachers, achieving a high score of 87.5%. The results indicate that the interactive pop-up storybook effectively enhances cognitive, social, and emotional engagement while instilling tolerance and social values. This study underscores the potential of culturally contextualized interactive media to strengthen holistic learning experiences, learning motivation, and the development of inclusive social character in early childhood.